Factors Related to the Implementation of Discharge Planning by Nurses in the Inpatient Ward of BLUD RSUD Meuraxa, Banda Aceh City - S, Muhammad Iqbal; Syukriadi, Syukriadi; Roslina, Roslina; Riza, Saiful (Institute Of Computer Science (IOCS), 2024)
The implementation of discharge planning is crucial in nursing care, as the continuity of care becomes an imperative that nurses must execute optimally, thereby influencing service quality. The implementation of discharge planning serves as a benchmark for continuous patient care from admission to discharge. The research aims to identify factors associated with the implementation of discharge planning by nurses in the ward. This research adopts a quantitative analytical design with a cross-sectional approach. The study was conducted from August 15th to 21st, 2023. The population consisted of all practicing nurses, totaling 272 nurses, with a sample size of 73 respondents selected using lottery technique. Data analysis was conducted using the chi-square test. The research findings indicate there is a relationship between motivation factors (p-value: 0.003), workload factors (p-value: 0.007), staffing factors (p-value: 0.002), and time factors with the implementation of discharge planning by nurses (p-value: 0.008). It is hoped that nurses can enhance their understanding of the importance of discharge planning, deliver comprehensive nursing care, and execute discharge planning comprehensively from admission to discharge, thus improving the quality of hospital services.